Pengaruh Variasi Diameter Filler Dan Kuat Arus Terhadap Kekuatan Tarik Hasil Pengelasan SMAW Material Stainless Steel 304 - Dimas Adi Perwira; Henry Widya Prasetya; Muh. Adib Kurniawan (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2021)
One of the railway facilities uses stainless steel as the main construction material. The method of joining stainless steel materials, especially the most widely used is the SMAW welding technique. The purpose of this study was to determine the tensile strength of SMAW welding joints on stainless steel 304 material with variations in diameter of rod filler as filler material an d variations in current from DC inverter electric welding machine. The diameter of rod filler as filler material is 1 mm, 2 mm and 3 mm. The variation of the current of the DC inverter of the electric welding machine is 70 A, 100 A and 120 A. The results show the highest tensile strength of the 304 stainless steel welded connection with an average tensile stress of 34.48 MPa on the current electric welding inverter. 120 A is used and the diameter of the rod filler is 2 mm. And the tensile strength of the welding connection of the 304 stainless steel material is the lowest with an average tensile stress of 17.01 MPa at the electric welding inverter current used is 70 A and the diameter of the rod filler is 3 mm.Keyword: SMAW welding, filler, current and stainless steel